EKSISTENSI KPK DALAM PEMBERANTASAN KORUPSI DI INDONESIA - Ruslan Abdul Gani (Jurnal LEX SPECIALIS, 2010)
AbstractRegarding the existence of the Corruption Eradication Commission this performance is virtually no doubt when compared with the investigator from the Police and the Attorney General. Already many big cases are successfully resolved by the Commission for Eradication of corruption such as Jambi Mes cases handled by the KPK by dragging a convict Secretary of Jambi Province, by dragging Zedra BLBI Abidin as the convict, the case of procurement of aircraft Heli Kopter in Aceh Governor Abdullah Puteh by dragging as Governor of Aceh, the case that menimpah Members of Parliament who called Al Amin Nasution of the land acquisition scandal in South Sumatra and Riau, and many other major cases successfully handled by the KPK. Unfortunately, behind the success of the Commission for Eradication of Corruption in heavy duty, there are parties who want to institute this body suver been waived .